Disposisi, Kehendak Bebas, dan Kontingensi - Silalahi, Ubat Pahala Charles (Studia Philosophica et Theologica, 2024)
This article discusses the long-standing philosophical challenge of integrating disposition, free will, and contingency. We place the above three realities into a coherent theoretical framework. Various disciplines have extensively studied the concepts of disposition, free will, and contingency. Nevertheless, their complex interrelationships still need to be more adequately explored. The result is a persistent dichotomy that gives rise to debates about causation, agency, and the reality of modalities. Thus, this article proposes a new framework called triadic relations to explain the mutual dependencies and emergent properties of the interaction of these fundamental ideas. The article uses a systematic synthesis approach of recent developments in dispositional essentialism, compatibilist theories of free will, and the metaphysics of the modal. We aim to show how dispositions provide the ontological foundation for free will and contingent possibilities. After all, free will operation actualizes specific potentials and introduces original novelty. This method offers an exciting resolution to the compatibilist libertarian debate by providing a new perspective on mental causation, moral responsibility, and the nature of contingency. Our findings suggest a dynamic ontology that transcends traditional philosophical categories. The findings redefine metaphysics, philosophy of mind, ethics, and interdisciplinary areas. Triadic relations emerge as a new paradigm for reconceptualizing the structure of reality and human agency to reshape the landscape of philosophical inquiry.